Electronic Word-of-mouth (E-WOM) In Social Media As A Predictor Of Investment Intention In Capital Market - Eka Putri Innayah; Vivin Maharani Ekowati; Achmad Sani Supriyanto; Masyhuri; Fuadah Binti Johari (Department of Management Faculty of Economics and Business Universitas Brawijaya, 2024)
Vol 20, No 4